Emergy and energy analysis as an integrative indicator of sustainability: A case study in semi-arid Canadian farmlands. (20th January 2018) - Fan, Jianling; McConkey, Brian G.; Janzen, H. Henry; Miller, Perry R.
Abstract: Agricultural is essential to feed the human world but it can also degrade the physical world. Therefore, we need widely-accepted metrics to assess how prospective practices influence sustainability. We hypothesized that emergy and energy analyses considered together provide a robust, comprehensive measure of sustainability, and evaluated this hypothesis using findings from two field studies in the semiarid prairie region of Canada: a systems experiment including nine different 3-yr cropping rotation systems and a stubble experiment involving five preceding crop stubbles treatments with three nitrogen (N) addition levels. The grain yield emergy transformities of rotation systems with pulses, ranging from 0.68 to 0.83 E+05 sej J −1, were 32% lower ( P  < 0.05) than rotations without pulses. Significantly lower grain transformity of durum wheat grown on pulse stubbles than grown on durum wheat stubble were observed for both the systems and stubble experiments, suggested a higher crop production efficiency conferred by previous pulse crops. The emergy sustainability index (ESI) of Fallow-Durum wheat-Pea (F-D-P) rotation (1.94) was 1.3–2.2 times that of other rotations, while the continuous rotations increased ESI from 1.00–1.11 to ESIΔQ of 2.00–2.21 by considering the storage increase (Δ Q ) of the system, i.e. soil organic carbon (SOC). The grain yield/energy input ratio (G/I) and energy output/energy input ratio (O/I) for F-D-P rotation (775 g MJ −1 and 12.9, respectively) were significantly ( P  < 0.05) higher than those of all other rotations for its low energy input, which was obtained at the cost of huge SOC decrease. Modified energy use efficiency indices, G/IΔSOC and O/IΔSOC, were proposed in the present study to include the effect of SOC change (ΔSOC) in energy use efficiency by regarding ΔSOC as energy input where the system depleted SOC and as energy output where SOC accumulated. The G/IΔSOC and O/IΔSOC ratios for continuous rotations were significantly ( P  < 0.05) higher than those of other rotations, indicating higher energy use efficiency in continuous rotation systems. Therefore, ESIΔQ and O/IΔSOC are recommended as sustainability indicators in emergy and energy analysis respectively, and we recommend that emergy and energy analysis should be done and considered together to have a more informative assessment of relative sustainability and efficiency of cropping systems. Highlights: Emergy and energy analysis should be considered together to assess sustainability. Crop diversification benefits durum wheat production efficiency and suitability. Considering SOC change in emergy and energy indices are highly recommended. Modified energy use efficiency indices are proposed by considering SOC change. Integrated analysis is more informative than independent emergy or energy analysis.